Magnetocarcinogenesis: Is there a mechanism for carcinogenic effects of weak magnetic fields? - Juutilainen, J; Herrala, M; Luukkonen, J; Naarala, J; Hore, P (Royal Society, 2018)
Extremely low frequency (ELF) magnetic fields have been classified as possibly carcinogenic, mainly based on rather consistent epidemiological findings suggesting a link between childhood leukaemia and 50-60 Hz magnetic fields from power lines. However, causality is not the only possible explanation for the epidemiological associations, as animal and in vitro experiments have provided only limited support for carcinogenic effects of ELF magnetic fields. Importantly, there is no generally accepted biophysical mechanism that could explain such effects. In this review, we discuss the possibility that carcinogenic effects are based on the radical pair mechanism (RPM), which seems to be involved in magnetoreception in birds and certain other animals, allowing navigation in the geomagnetic field. We review the current understanding of the RPM in magnetoreception, and discuss cryptochromes as the putative magnetosensitive molecules and their possible links to cancer-relevant biological processes. We then propose a hypothesis for explaining the link between ELF fields and childhood leukaemia, discuss the strengths and weaknesses of the current evidence, and make proposals for further research.